Serum Prohepcidin Levels Are Lower in Patients with Atrophic Gastritis - Hyung-Keun Kim; Eun-Chul Jang; Ju-Ok Yeom; Sun-Young Kim; Hyunjung Cho; Sung Soo Kim; Hiun-Suk Chae; Young-Seok Cho (Gastroenterology Research and Practice)
Background/Aim. Hepcidin, an iron regulatory hormone, is increased in response to inflammation and some infections. We investigated the relationships among serum prohepcidin, iron status, Helicobacter pylori infection status, and the presence of gastric mucosal atrophy. Methods. Seventy subjects undergoing esophagogastroduodenoscopy underwent multiple gastric biopsies, and the possibility of H. pylori infection and the degree of endoscopic and histologic gastritis were investigated. In all subjects, serum prohepcidin and iron parameters were evaluated. Results. No correlations were observed between serum prohepcidin levels and the other markers of anemia, such as hemoglobin, serum iron, ferritin, and total iron binding capacity. Serum prohepcidin levels were not significantly different between the H. pylori-positive group and the H. pylori-negative group. Serum prohepcidin levels in atrophic gastritis patients were significantly lower than those in subjects without atrophic gastritis irrespective of H. pylori infection. Conclusion. Serum prohepcidin levels were not altered by H. pylori infection. Serum prohepcidin levels decrease in patients with atrophic gastritis, irrespective of H. pylori infection. It suggests that hepcidin may decrease due to gastric atrophy, a condition that causes a loss of hepcidin-producing parietal cells. Further investigations with a larger number of patients are necessary to substantiate this point.